Upaya Peningkatan Pengetahuan Terhadap Pentingnya Pemakaian dan Pemeliharaan Gigi Tiruan pada Masyarakat Desa Ma’rang - Amiruddin, Maqhfirah; Andi Tenri Biba; Chusnul Chotimah; Utama, Mohammad Dharma (Idea Pengabdian Masyarakat, 2022)
Dentures are devices made to replace missing teeth and the surrounding soft tissue. The use of dentures will restore aesthetic function, masticatory function, speech function, and maintain the health of the surrounding tissue. Denture maintenance is very important because it will determine the success of using dentures. The behavior of maintaining dental and oral hygiene that is not good from users of removable dentures can cause disease in the oral cavity. The purpose of this service is to increase knowledge of the community in Ma’rang Village, Pangkep Regency, on the importance of using and maintaining dentures. The method of implementing the service is by conducting direct counseling to the elderly in Ma’rang Village. Education with power point media, poster installation, educational video screening, and distribution of leaflets to each counseling participant as well as questions and answers and discussions. The service activities took place effectively and the community was very enthusiastic about questions about the use and maintenance of dentures. The elderly community in Ma’rang Village is very grateful for this service activity, in addition to increasing knowledge about the use and maintenance of dentures, the community also hopes that this activity will be able to continue in the future.